1984
DOI: 10.1104/pp.75.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysin Is a Suitable Protease for Probing the Surface of Intact Pea Chloroplasts

Abstract: ABSTRACISeveral proteases, ie., pronase, a mixture oftrypsin and chymotrypsin, and thermolysin were screened as potential surface probes of isolated intact pea (Pisum satiium var Laxton's Progress No. 9) chloroplasts. Of these, only thermolysin met the criteria of a suitable probe. Thermolysin destroyed outer envelope polypeptides, but did not affect inner envelope polypeptides, envelope permeability properties or such chloroplast activities as metabolite transport and 02 evolution.Methods involving protease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
203
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(207 citation statements)
references
References 15 publications
(21 reference statements)
3
203
1
Order By: Relevance
“…The results of SDS-PAGE of purified envelope membranes are shown in Fig. 1 and demonstrate the purity of the respective membrane population and the typical distribution of envelope marker proteins (Cline et al 1984). As can be seen in lanes 1-5, when [7-32p]ATP is used as the phosphoryl donor, each of the chloroplast fractions yields a distinctive pattern of labeled polypeptides.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The results of SDS-PAGE of purified envelope membranes are shown in Fig. 1 and demonstrate the purity of the respective membrane population and the typical distribution of envelope marker proteins (Cline et al 1984). As can be seen in lanes 1-5, when [7-32p]ATP is used as the phosphoryl donor, each of the chloroplast fractions yields a distinctive pattern of labeled polypeptides.…”
Section: Resultsmentioning
confidence: 78%
“…1 ; Keegstra and Yousif 1986). Chloroplasts were protease-treated with thermolysin at 200 gg protease, mg ~ chlorophyll (Joyard et al 1983;Cline et al 1984) and separated inner and outer envelope membranes were purified from these plastids (Keegstra and Yousif 1986). Soluble chloroplast proteins were isolated after hypotonic lysis of purified intact chloroplasts and subjected to centrifugation at 50000.g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…One of these proteins had a size of around 86 kDa and was susceptible to thermolysin treatment (Cline et al, 1984;Joyard et a/., 1983). Antibodies which we have raised against the outer envelope protein of 86 kDa (OEP 86) recognized the high molecular weight component in fractions 15-1 8 of the sucrose gradient ( Figure 5).…”
Section: Identification Of Two Proteins In the Complexmentioning
confidence: 99%
“…Furthermore, it has been shown that protease treatment of intact chloroplasts diminishes the import, indicating the involvement of surface exposed proteins [7]. Much less attention has been given to the possible roles of envelope lipids.…”
Section: Introductionmentioning
confidence: 99%